2009
DOI: 10.1097/nmd.0b013e3181a20849
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alliance in the Relationship Between Therapist Competence and Outcome in Brief Psychodynamic Psychotherapy

Abstract: Therapist competence is a key variable for psychotherapy research. Empirically, the relationship between competence and therapeutic outcome has shown contradictory results and needs to be clarified, especially with regard to possible variables influencing this relationship. A total of 78 outpatients were treated by 15 therapists in a very brief 4-session format, based on psychoanalytic theory. Data were analyzed by means of a nested design using hierarchical linear modeling. No direct link between therapist co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 42 publications
3
13
0
1
Order By: Relevance
“…Therefore, the therapeutic alliance can be considered as an important mediator for the relationship between therapist competence and treatment outcome. Some studies support this perspective and found that therapeutic alliance mediates the relationship between competence and outcome (e.g., Barber et al, 1996;Despland et al, 2009;Weck et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, the therapeutic alliance can be considered as an important mediator for the relationship between therapist competence and treatment outcome. Some studies support this perspective and found that therapeutic alliance mediates the relationship between competence and outcome (e.g., Barber et al, 1996;Despland et al, 2009;Weck et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…In empirical research, a close association between therapist adherence and competence was found (Barber, Triffelman, & Marmer, ), which conforms with the notion that adherence is a precondition for competence (Waltz et al ., ). Furthermore, both theoretical reflections and empirical research suggest that therapist competence is a precondition for a good therapeutic alliance (Barber, Crits‐Christoph, & Luborsky, ; Despland et al ., ) and that a good therapeutic alliance is in turn the basis for a positive adherence–outcome relationship (Barber et al ., ; McLeod, Southam‐Gerow, Tully, Rodríguez, & Smith, ). Accordingly, previous research considered linear and curvilinear relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This principle has also been researched in a series of psychotherapy studies (for reviews, see Lambert & Ogles, 2004;Martin, Garske, & Davis, 2000;and Wampold, 2001; for the link between therapist competence, therapeutic alliance, and outcome, see the previously cited study by Despland et al, 2009). In the case of Caroline, I applied Plan Analysis, an integrative individualized procedure of case conceptualization independent of any specific psychotherapy approach (Caspar, 2007(Caspar, , 2009, in which I focused in particular on Caroline's emotional and relationship stakes in the psychotherapy.…”
Section: Principle 2: Quality Of the Therapeutic Relationshipmentioning
confidence: 99%
“…Generally, then, in "third way" treatment, therapist competence involves both the ability to adhere to the manual and the judgment to know when and how to deviate from it. Competence implies the therapist's "skillfulness in providing a therapeutic milieu … in applying recognized techniques or methods consistent with the goals of treatment," as defined by Shaw et al (1999, p. 838), and as empirically supported by several studies, e.g., by Despland et al (2009). Specifically, in accordance with Shaw's definition, the Despland et al study found that therapist competence in the techniques of psychodynamic psychotherapy was not directly related to therapeutic outcome, but was moderated by the quality of the therapeutic alliance.…”
Section: Introductionmentioning
confidence: 99%